Village Government; Institutions THE ROLE OF THE VILLAGE GOVERNMENT IN THE DEVELOPMENT OF TOURISM VILLAGE INSTITUTIONS IN CISADAP VILLAGE, CIAMIS DISTRICT, CIAMIS REGENCY: Village Government; Institutions; Tourism Villages; Village-Owned Enterprises. - Arie Budiawan; Elin Nurlianti; Afrizal (Galuh International Journal of Community Service and Development, 2025)
The development of tourism villages represents a strategic approach to rural development by optimizing local potential and community empowerment. This community service activity aims to strengthen tourism village institutions through Village Government assistance in Cisadap Village, Ciamis District, Ciamis Regency. The assistance focuses on improving institutional governance, enhancing human resource capacity, and optimizing agribusiness-based economic potential, particularly through Village-Owned Enterprises. This activity employs a qualitative exploratory approach with participatory methods, including observation, interviews, documentation, and community-based mentoring. The results demonstrate that institutional strengthening has been implemented through the establishment of formal governance structures involving the Village Government, Tourism Awareness Group (Pokdarwis), and BUMDes. However, significant challenges persist in operational governance, such as limited Standard Operating Procedures, low managerial capacity, and suboptimal digitalization of administrative systems. The Village Government plays a central role in facilitating regulatory development, capacity building, and multi-stakeholder coordination. Strengthening efforts include specialized training programs, organizational restructuring, digital governance development, and expanding partnerships with external stakeholders, including local governments, universities, and the private sector. A SWOT analysis indicates that while Cisadap Village possesses robust tourism potential, it faces critical weaknesses in human resources, infrastructure, and institutional management. The findings highlight that integrating regulatory strengthening, community empowerment, and collaborative governance is essential for developing a sustainable tourism village. In conclusion, Village Government-assisted institutional strengthening serves as a key strategy to transform Cisadap Village into an independent, competitive, and sustainable tourism destination. This model emphasizes that synergy between local authorities and community groups is fundamental for long-term rural economic resilience.